The Inca fountains. A cultural landscape of dominance in the province of Cañar, Ecuador - Guayasamín Ortiz, Dayuma (2021)
The current province of Cañar in Ecuador was the political and economic center of the Cañari culture during the Integration period (500 to 1500 AD). With the expansion of the Tawantinsuyo, the Incas established different strategies for political and ideological dominance over the local populations of Chinchaysuyo, which were expressed through a cultural appropriation of certain geographic spaces, using a specific architecture and toponymy that allowed replicating the idea of ‘another Cuzco’. In the archaeological complexes of Ingapirca and Coyoctor in Cañar, there are carved structures in rocky outcrops known as Baños del Inca. In reality, these were Inca’s structures and places for purification and worship of water. Also, spaces to legitimize Inca domination through the myth of origin and the implementation of festivities such as Situa.